2013
DOI: 10.1212/wnl.0b013e31829bfe41
|View full text |Cite
|
Sign up to set email alerts
|

Limited short-term prognostic utility of cerebral NIRS during neonatal therapeutic hypothermia

Abstract: During day 3 of cooling and during rewarming, loss of physiologic variability (by systemic NIRS) and invariant, discontinuous aEEG patterns predict poor short-term outcome in neonates with HIE. These parameters, but not cerebral NIRS, may be useful to identify infants suitable for studies of adjuvant neuroprotective therapies or modification of the duration of cooling and/or rewarming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
30
0
10

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 36 publications
3
30
0
10
Order By: Relevance
“…In their later work, they included the entire 72-h cooling period. Nevertheless, NIRS variables did not differentiate between those with normal and poor 18-month outcomes [24]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their later work, they included the entire 72-h cooling period. Nevertheless, NIRS variables did not differentiate between those with normal and poor 18-month outcomes [24]. …”
Section: Discussionmentioning
confidence: 99%
“…The strengths of our study are: (a) the number of studied neonates, compared to other published studies of aEEG and NIRS in infants with HIE [8,9,10,23,24]; (b) the homogeneity of our patient population (only HIE II); (c) the detailed analysis of aEEG (including analysis of SWC and seizures); and (d) the combination of aEEG with NIRS data over a total of 102 h.…”
Section: Discussionmentioning
confidence: 99%
“…Nitin K. Sethi, New York: Lamberts et al 1 reported on postictal generalized EEG suppression (PGES) inconsistency in patients with multiple convulsions. PGES following convulsive seizures occurs in some but not all patients.…”
mentioning
confidence: 99%
“…PGES following convulsive seizures occurs in some but not all patients. 1,2 Patients with PGES are at higher risk for sudden unexpected death in epilepsy (SUDEP), especially if tonic-clonic seizures are uncontrolled; they are on antiepileptic drug (AED) polypharmacy; AED levels are subtherapeutic, indicative of noncompliance; they live alone; or they have coexisting cognitive deficits. 2,3 While the link between PGES and SUDEP is intriguing, there are more variables to be considered than simply the duration or consistency of suppression on EEG after a convulsion.…”
mentioning
confidence: 99%
See 1 more Smart Citation